æ±‰è¯ä¸Žå°å°¼è¯æˆè¯ä¸çš„äº”ç§æ¤ç‰©æ–‡åŒ–æ„ä¹‰å¯¹æ¯”åˆ†æž - Afrina, Uray; Thamrin, Lily; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Idioms are the essential part ofÂ Mandarin and Indonesian. Plant idiom have a lively and profound meaning because it is based on plant imagery.This paper used